AKTIVITAS ANTIJAMUR KOMBINASI EKSTRAK ETANOL DAUN MANGGA BACANG (MANGIFERA FOETIDA L.) DAN DAUN BIDARA (ZIZIPHUS MAURITIANA L.) TERHADAP CANDIDA ALBICANS - Dini Mardhiyani; Kony Putriani (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2021)
Along with increasing life expectancy, the community tries to find solutions to health problems. One of the health problems that occur in humans is caused by fungi. Candida albicans is one of the fungi that can be found in humans. Candida albicans are normal flora in the vagina, digestive tract, and oral cavity. Nevertheless, it can change into a pathogen and cause changes in the host. Based on compound contained in leaf of mango bacang and leaf of bidara, they have antifungal effect. This study aims to determine the antifungal activity of single ethanol extract of mango bacang leaves and bidara leaves with a combination of bidara leaves ethanol extract and ethanol extract of mango bacang leaves against Candida albicans. The method of this study begins with collecting mango bacang leaves and bidara leaves then extracted maceration with ethanol solvents. The antifungal activity is tested with the disk diffusion method using potato dextrose media. Based on the results of the hypothesis test obtained a significance value of 0.010 <0.05, there was a difference in the diameter of the inhibition zone against the growth of Candida albicans due to a single giving and variations in the combination of ethanol mango bacang leaves and bidara leaves ethanol extract. Extract single antifungal activity after combined experienced a minimum increase of 1.2%. The conclusion of this study shows that the combination of ethanol extract of bacang mango leaves with bidara leaves ethanol extract has a larger inhibiting zone than a single extract and shows the synergy effect. The use of bacang mango leaves as anti-fungal is recommended in combination with bidara leaves.